English Guiding Video for “Visa on Arrival Extension in One Day Service “at Cilacap Class I Immigration Office - Rafif Dzaky Alauddin Cahya (Jurnal Vokasia, 2023)
The job training, at Cilacap Class I Immigration Office, Central Java, wascarried out from April 3rd, 2023 to May 3rd, 2023. The main task was producinga guiding video of "Visa on Arrival Extension in One Day Service" The videowas made in English to make it easier for foreigners to understand. Furthermore,another task was assisting the Immigration Information Technology Division inthe development of infographics regarding immigration services, intended forpublication on the social media platforms of Cilacap Class I Immigration Office.The process of creating a guiding video included planning, script writing,shooting, and post production editing. The guiding video was reviewed andrevised before being approved for publication on Cilacap Immigration Office'ssocial media platforms, including Instagram, Facebook, and YouTube. It aims toprovide information and assistance to foreigners in the process of Visa on ArrivalExtension in One Day Service, and improve the services provided by the CilacapClass I Immigration Office.Obstacles encountered during the job training and production of the guidingvideo encompassed miscommunication, incongruity of creative visions, adverseweather conditions, and the presence of a large number of visitors at CilacapImmigration Office. Solutions were implemented such as comprehensivemeetings for mutual understanding, discussing creative visions in detail,checking the weather forecast, and scheduling shooting out of peak hours.Key words: Immigration, Visa on Arrival Extension, Tourism, Guiding Video.